Candida albicans Rim13p, a Protease Required for Rim101p Processing at Acidic and Alkaline pHs - Li, Mingchun (American Society for Microbiology, 2004)
Candida albicans is an important commensal of mucosal surfaces that is also an opportunistic pathogen. This organism colonizes a wide range of host sites that differ in pH; thus, it must respond appropriately to this environmental stress to survive. The ability to respond to neutral-to-alkaline pHs is governed in part by the RIM101 signal transduction pathway. Here we describe the analysis of C. albicans Rim13p, a homolog of the Rim13p/PalB calpain-like protease member of the RIM101/pacC pathway from Saccharomyces cerevisiae and Aspergillus nidulans, respectively. RIM13, like other members of the RIM101 pathway, is required for alkaline pH-induced filamentation and growth under extreme alkaline conditions. Further, our studies suggest that the RIM101 pathway promotes pH-independent responses, including resistance to high concentrations of lithium and to the drug hygromycin B. RIM13 encodes a calpain-like protease, and we found that Rim101p undergoes a Rim13p-dependent C-terminal proteolytic processing event at neutral-to-alkaline pHs, similar to that reported for S. cerevisiae Rim101p and A. nidulans PacC. However, we present evidence that suggests that C. albicans Rim101p undergoes a novel processing event at acidic pHs that has not been reported in either S. cerevisiae or A. nidulans. Thus, our results provide a framework to understand how the C. albicans Rim101p processing pathway promotes alkaline pH-independent processes.